MAKNA INTERPERSONAL DALAM INTERAKSI DOSEN DAN MAHASISWA DI LINGKUNGAN PERGURUAN TINGGI DI JAYAPURA - Paranoan, Emon; K, Komari (DINAMIS, 2015)
The purpose of this research is to find out how are the verbal communication from theinteraction between students and lecturer in class. This research also finds out the influences of thesocial variation in interacting students and lecturer in class. Data are taken in two differentuniversities they are University of Sains and Technology Jayapura and University of Cenderawasih. Alldata are taken from audio recording, the writer records all the verbal interaction which utteranced bothof students and lecturer. Verbal reactions from the interaction in class are analyzed using criticaldiscourse analysis theory based on the principles of sytemic function grammar. This research focuseson the inter personal meaning found in the text by paying attention to the aspect mood. It was foundthat class interaction between students and lecturer are largely dominated by lecturer. It can beconcluded then that interpersonal realtionship is still very much dominated by the lecturers becausethey have managerial authoriy as well as the knowledge in class, students did not give initationtrhough interaction in class since they have weakness power. This research also found then that thelecturers did statement and question verbal realization and students did answer of all the inization thatlecturers gave to the students since the student realize they have no managerial aothority as well asthe knowledge in class.